PERBANDINGAN LAJU KOROSI PAKU BETON PADA MEDIUM AIR PDAM DAN AIR LIMBAH AC (AIR CONDICIONER) - Tajudin, Suaib; Rahmaniah, Rahmaniah; Ihsan, Ihsan (Universitas Islam Negeri Alauddin Makassar, 2020)
The purpose of this study was to compare the corrosion rate of concrete nails with the medium of PDAM water and AC wastewater. The method used is the weight loss method. Immersion of the sample is carried out for 30 days and measurements are carried out and corrosion rate analysis is carried out every 10 days. Nail corrosion rate with PDAM water medium was obtained at 4.06 × 10-7 mm / year, while the corrosion rate of nails with AC wastewater medium based on variations in PK size and temperature size regulation on each AC obtained the largest corrosion rate on AC PK 1 ½ with a temperature of 18oC 4 × 10-7 mm / year, a temperature of 190C 2.66 × 10-7 mm / year, 20oC, 5.77 × 10-7 mm / year and a temperature of 21oC, 5.88 × 10-7 mm / year. AC PK 2 with a temperature of 19oC, 5.26 × 10-7 mm / year, a temperature of 20oC, 7.97 × 10-7 mm / year, a temperature of 21oC, 4.95 × 10-7 mm / year and a temperature of 22oC 3.49 × 10 -7 mm / year. For AC PK 1 with a temperature of 20oC, 3.77 × 10-7 mm / year, a temperature of 21oC 5.74 × 10-7 mm / year, a temperature of 22 oC, 8.11 × 10-7 mm / year and a temperature of 23oC 8.96 × 10-7 mm / year.